ASIA syndrome: Adverse reaction or autoimmunity?. Issue 4 (April 2022) - André, Diogo; Gouveia, Fabiana; Nascimento, Rafael; Luís, Helena; Caldeira, Mónica; Ferreira, Caldeira; Chaves, António José
Introduction: Adjuvant-Induced Autoimmune / Auto-inflammatory Syndrome (ASIA) is an immune-mediated condition by the exposure of material previously considered inert, such as silicone, aluminum salts, mineral oils, hyaluronic acid and metallic implants. In addition to a genetic component, there is a risk of development of an undifferentiated connective tissue disease, which varies clinically and laboratorially depending on the adjuvant material used. Patients and methods: This paper addresses two cases reported, in caucasian subjects, born and residents in Madeira Island, Portugal. In this article are described two different histological patterns occurring in ASIA patients, due to mammoplasty with silicone. Conclusion: Although ASIA does not meet the diagnostic requirements for connective tissue disease, there is a close relationship with the development of autoimmune conditions. These cases aim to alert the medical community to the existence of this entity, encourage the notification of situations arising from exposure to adjuvants and investigate the presence of a genetic predisposition and a suggestive histological pattern in excisional biopsies of satellite adenomegalies.